PENGARUH STORE ATMOSPHERE, PRODUCT, DAN PROMOTIONAL MIX TERHADAP KEPUTUSANPEMBELIAN BARANG DI DISTRO (Studi Kasus pada Noisy Clothing Malang) - Fatkhul Akmal Maulana; Rois Arifin; Achmad Agus Priyono (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACTThe current storage phenomenon, product mix and promotion become the main discussion topic in this research because it able to give contribution to purchasing decision of goods either individually or simultaneously in doing marketing strategy.The research was conducted in Malang Apparel Malang. Tujan this research is for more information and prefer mix, product and promotion for purchasing decision of goods in distros partially or simultaneously. Variables used in this study are attributes of stores, products and. As the dependent variable. The sample used in this research is 90% of noise consumers using accidental method. Methods of research data with questionnaires distribution. Analysis using SPSS 14.0 for windows program.The results of this study indicate a significant storage environment in purchasing decisions in the distribution of goods, a significant product to the decision of purchasing goods in distribution decisions and promotion mix of significant to the purchase of goods in distribution, shop atmosphere, product and promotion mix. Simultaneously on the goods in the distribution.Keywords : Store Atmosphere, Product, Mixed Promotion, DecisionPurchaseof Goods in Distro